EML1‐associated brain overgrowth syndrome with ribbon‐like heterotopia. Issue 4 (11th November 2019) - Oegema, Renske; McGillivray, George; Leventer, Richard; Le Moing, Anne‐Gaëlle; Bahi‐Buisson, Nadia; Barnicoat, Angela; Mandelstam, Simone; Francis, David; Francis, Fiona; Mancini, Grazia M. S.; Savelberg, Sanne; van Haaften, Gijs; et al.
Abstract: EML1 encodes the protein Echinoderm microtubule‐associated protein‐like 1 or EMAP‐1 that binds to the microtubule complex. Mutations in this gene resulting in complex brain malformations have only recently been published with limited clinical descriptions. We provide further clinical and imaging details on three previously published families, and describe two novel unrelated individuals with a homozygous partial EML1 deletion and a homozygous missense variant c.760G>A, p.(Val254Met), respectively. From review of the clinical and imaging data of eight individuals from five families with biallelic EML1 variants, a very consistent imaging phenotype emerges. The clinical syndrome is characterized by mainly neurological features including severe developmental delay, drug‐resistant seizures and visual impairment. On brain imaging there is megalencephaly with a characteristic ribbon‐like subcortical heterotopia combined with partial or complete callosal agenesis and an overlying polymicrogyria‐like cortical malformation. Several of its features can be recognized on prenatal imaging especially the abnormaly formed lateral ventricles, hydrocephalus (in half of the cases) and suspicion of a neuronal migration disorder. In conclusion, biallelic EML1 disease‐causing variants cause a highly specific pattern of congenital brain malformations, severe developmental delay, seizures and visual impairment.